Combination of electromagnetic navigation bronchoscopy-guided biopsy with a novel staining for peripheral pulmonary lesions - Qian, Kai (World J Surg Oncol, 2019)
BACKGROUND: The diagnosis of peripheral pulmonary lesions (PPLs) is a challenging task for pulmonologists, especially for small PPLs. Conventional localization of these small PPLs, which are > 1 cm away from the visceral pleura in operation, is quite difficult. Currently used methods inevitably damage the visceral pleura and may cause a series of complications, such as pneumothorax and hemothorax. Hence, the present study aimed to find out an intraoperative localization method with no damage to the visceral pleura. METHODS: We retrospectively reviewed 21 patients with PLLs who underwent electromagnetic navigation bronchoscopy (ENB)-guided biopsy plus a new methylene blue staining with the help of massage (Massage Staining) in our department between August 2017 and December 2018. RESULTS: The median age of these 21 patients was 51.3 ± 2.1 years. The diameter of the PPLs was 8.2 ± 2.3 mm. The rate of successful biopsy was 76.2%, and the rate of excellent or satisfactory of Massage Staining was 81.0%, while all lesions of these 21 cases were included in the range of staining, and the median distance from the edge of the stained site to the edge of the lesion was 29 ± 18 mm. The duration of ENB-guided biopsy plus Massage Staining was 26.7 ± 5.3 min, and the intraoperative blood loss was 3.3 ± 1.5 ml. No pneumothorax, hemorrhage, and tracheal injury occurred intraoperatively. CONCLUSIONS: The ENB-guided biopsy combined with Massage Staining is an innovative one-stop strategy designed to enhance the precision of thoracic surgery. The Massage Staining avoids damage to the visceral pleura, causes the low incidence of complications, but yields precise localization of PPLs.